LUCIAN BLAGA DANS L’ESPACE EUROPÉEN: POUR UNE POÉSIE PHILOSOPHIQUE ? LE DANGER DES LECTURES DÉFORMANTES - Carmen-Ecaterina AŞTIRBEI (Diversitate si Identitate Culturala in Europa, 2011)
Our study is an analysis of Lucian Blaga’s poetry in the European culture, especially in the French and francophone milieu, through the existing translations. Blaga is an important figure of the 20th century: as he was, at the same time, a poet, philosopher, essayist, dramatic author, and novelist, his work is difficult to classify and runs the risk of distorting interpretations. The key-question of our debate will have in view the literary genre to which Blaga’s poetry may belong: can we really talk about “philosophical poetry”, as it was written at the same time as the construction of Blaga’s philosophical system? We consider that Blaga’s poetry and philosophy are analogous, but not to be confused; in this context, we prefer the syntagm “conceptual poetry” and will justify our choice by the fact that this poetry is built on theories concerning knowledge, the original phenomenon and the discovery of the cosmic mystery.